A Prospective, Randomized, Open-Label Study to Evaluate Two Management Strategies for Gastrointestinal Symptoms in Patients Newly on Treatment with Dabigatran. Issue 2 (December 2016) - O'Dea, Daniel; Whetteckey, Jacqueline; Ting, Naitee
Abstract Introduction In the pivotal RE-LY trial, dabigatran etexilate (DE) at the dose of 150-mg twice daily (BID), significantly reduced total stroke and ischemic stroke compared with warfarin in patients with non-valvular atrial fibrillation (NVAF), while the 110-mg BID dose had efficacy equivalent to warfarin, and major bleeds were significantly reduced. Both DE regimens were generally well tolerated; however, approximately 4% of the patients discontinued treatment with DE due to gastrointestinal (GI) discomfort. Methods Clinical trial NCT01493557 was a multicenter, randomized, active control, open-label study to assess the efficacy of two simple GI symptom (GIS) management strategies in DE-treated patients who developed GIS: (1) concurrent treatment with the proton pump inhibitor pantoprazole (DE-P), or (2) ingestion of DE after a meal (DE-M). Patients were initially randomized to either GIS management strategy. If the first did not resolve their GIS, patients had the option to "add on" the alternative strategy. Results A total of 1067 patients with NVAF received DE therapy BID for 3 months (United States, 150-mg or 75-mg; Canada, 150-mg or 110-mg). Of these, 117 (11%) patients reported GIS and were randomized to one of two GIS management strategies. At 4 weeks, a significantly higher rate of complete or partial effectiveness was observed in patients on DE-P than in those receiving DE-M, [50/58 (86.2%) versus 40/59 (67.8%), respectively;p  = 0.0273]. Patients with ongoing GIS were asked to "add on" the alternate strategy for an additional 4 weeks. Overall, 92/117 (78.6%) of randomized patients experienced complete or partial effectiveness using either the initial strategy or a combination of the two strategies: DE-P, 47 (81.0%); and DE-M, 45 (76.3%, no significant difference) (by initial strategy). Conclusion The majority of patients enrolled either did not experience GIS at all, or their GIS resolved using either one individually, or a combination of the two strategies described. Trial registration http://www.ClinicalTrials.gov identifier: NCT01493557.